เภสัชจลนศาสตร์ประชากรของยาทาโครลิมุสในผู้ป่วยไทยที่ได้รับการปลูกถ่ายไต - สาวิตรี ไพรสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Objectives: The aim of this study was to develop a population pharmacokinetic model to estimate the value of tacrolimus apparent oral clearance (CL/F) in Thai kidney transplant patients. Methods: Retrospective and prospective descriptive study was conducted in 77 kidney transplant patients who were receiving tacrolimus at King Chulalongkorn Memorial Hospital, Bangkok, Thailand. Drug concentration data and relevant patient informations were obtained from clinical patient medication profiles and routine therapeutic drug monitoring records. In addition, blood samples were collected (26 kidney transplant patients) at pre-dose, 1, 2, 4, 6, 8 and 12 hours after drug administration for pharmacokinetics analysis. A total of 959 whole blood concentrations were analyzed for population pharmacokinetic modeling by Nonlinear Mixed Effect Model (NONMEM) computer program. Results: Population pharmacokinetic modeling of tacrolimus was best described by a one compartment model with first order absorption. The population estimate of tacrolimus CL/F was found to be 21.3 L/h. The influence of significant covariates on CL/F were duration of tacrolimus therapy (p<0.05), hemoglobin levels (p<0.05) and albumin levels (p<0.05). The population pharmacokinetic equation that predicted CL/F of tacrolimus, was CL/F = 100 x DOT-0.0698 x HB-0.498. Additional, the simple equation of CL/F that was analyzed by linear covariate model, was CL/F = 39.4 – 0.955 HB – 0.00194 DOT – 1.59 ALB, where CL/F was tacrolimus apparent oral clearance (L/h), DOT was duration of tacrolimus therapy (days), HB was hemoglobin levels (g/dL) and ALB was albumin levels (g/dL). The duration of tacrolimus therapy, hemoglobin levels and albumin levels were significant covariates influencing tacrolimus CL/F. These factors should be considered whenever designing tacrolimus dosage in kidney transplant patients.